Typology of corporate liquidity managers from behavioral finance perspective - Korzeniowska, Dominika (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The paper presents a typology of professionals who deal with liquidity management in enterprises and is based on meta analysis of the results of the qualitative research led by the author. This typology reflects managers‟ susceptibility to selected decision traps and their reflection about non-economic determinants that may influence decision-making process.